The Role of Product Quality and Pricing Strategies in Enhancing Purchase Decisions - M. Fahmi Ramadan; Atika Aini Nasution; Zahara Meutia (Outline Journal of Economic Studies, 2026)
Purpose: This study aims to analyze the partial and simultaneous effects of product quality and price on purchasing decisions for Honda motorcycles at PT. Aksara Motor Medan. Methods: The research employs a quantitative approach using multiple linear regression analysis. Product quality and price are treated as independent variables, while purchasing decisions serve as the dependent variable. The population consists of 133 consumers, with a sample of 100 respondents determined using the Slovin formula. Results: The findings indicate that product quality has a positive and significant partial effect on purchasing decisions (t-count = 4.162 > t-table = 0.806; significance = 0.000 < 0.05). Similarly, price also shows a positive and significant partial effect (t-count = 5.284 > t-table = 0.806; significance = 0.000 < 0.05). Furthermore, product quality and price simultaneously have a significant effect on purchasing decisions, as indicated by a significance value of 0.000 < 0.05. Conclusions: Both product quality and price significantly influence purchasing decisions, either partially or simultaneously, highlighting their importance in shaping consumer behavior at PT. Aksara Motor Medan. Originality/value: This study provides empirical evidence on the combined role of product quality and pricing strategies in influencing motorcycle purchasing decisions within a local dealership context.